Does board cultural diversity contributed by foreign directors improve firm performance? Evidence from Australia - Olga Dodd; Bowen Zheng (Journal of Risk and Financial Management, 2022)
Australian firms hire an increasing number of foreign directors who bring various cultural perspectives to their boards' conversations. We evaluate the effect of board cultural diversity contributed by foreign directors on firm performance for a sample of Australian companies, constituents of ASX200. We employ Hofstede's six cultural dimensions to estimate board cultural diversity. We document a positive relationship between board cultural diversity and firm performance as measured by Tobin's q and ROA after controlling for various board and firm characteristics. This suggests that more culturally diverse boards may bring benefits to their firms that outweigh the potential costs of conflict and miscommunication caused by cultural differences. Our finding holds after controlling for firm and time fixed effects, implementing an instrumental variable approach, controlling for a firm's foreign operations and presence, and using alternative cultural diversity measures. We find that not all aspects of cultural differences matter, and it is the diversity in masculinity, uncertainty avoidance, and long-term orientation dimensions that positively determine firm performance. This finding on the positive effect of board cultural diversity for Australian firms contrasts with the evidence from other countries, highlighting that the value of cultural diversity can differ across countries and over time.
Keywords: 650; firm performance; board of directors; cultural diversity; foreign directors; nationality diversity